Net Ultrafiltration Prescription and Practice Among Critically Ill Patients Receiving Renal Replacement Therapy: A Multinational Survey of Critical Care Practitioners. Issue 2 (February 2020) - Murugan, Raghavan; Ostermann, Marlies; Peng, Zhiyong; Kitamura, Koichi; Fujitani, Shigeki; Romagnoli, Stefano; Di Lullo, Luca; Srisawat, Nattachai; Todi, Subhash; Ramakrishnan, Nagarajan; Hoste, Eric; Puttarajappa, Chethan M.; et al.
Abstract : Objectives: To assess the attitudes of practitioners with respect to net ultrafiltration prescription and practice among critically ill patients with acute kidney injury treated with renal replacement therapy. Design: Multinational internet-assisted survey. Setting: Critical care practitioners involved with 14 societies in 80 countries. Subjects: Intensivists, nephrologists, advanced practice providers, ICU and dialysis nurses. Intervention: A cross-sectional survey. Measurement and Main Results: Of 2, 567 practitioners who initiated the survey, 1, 569 (61.1%) completed the survey. Most practitioners were intensivists (72.7%) with a median duration of 13.2 years of practice (interquartile range, 7.2–22.0 yr). Two third of practitioners (71.0%; regional range, 55.0–95.5%) reported using continuous renal replacement therapy with a net ultrafiltration rate prescription of median 80.0 mL/hr (interquartile range, 49.0–111.0 mL/hr) for hemodynamically unstable and a maximal rate of 299.0 mL/hr (interquartile range, 200.0–365.0 mL/hr) for hemodynamically stable patients, with regional variation. Only a third of practitioners (31.5%; range, 13.7–47.8%) assessed hourly net fluid balance during continuous renal replacement therapy. Hemodynamic instability was reported in 20% (range, 20–38%) of patients and practitioners decreased the rate of fluid removal (70.3%); started or increased the dose of a vasopressor (51.5%); completely stopped fluid removal (35.8%); and administered a fluid bolus (31.6%), with significant regional variation. Compared with physicians, nurses were most likely to report patient intolerance to net ultrafiltration (73.4% vs 81.3%; p = 0.002), frequent interruptions (40.4% vs 54.5%; p < 0.001), and unavailability of trained staff (11.9% vs 15.6%; p = 0.04), whereas physicians reported unavailability of dialysis machines (14.3% vs 6.1%; p < 0.001) and costs associated with treatment as barriers (12.1% vs 3.0%; p < 0.001) with significant regional variation. Conclusions: Our study provides new knowledge about the presence and extent of international practice variation in net ultrafiltration. We also identified barriers and specific targets for quality improvement initiatives. Our data reflect the need for evidence-based practice guidelines for net ultrafiltration. Abstract : Supplemental Digital Content is available in the text.